(3fhGOQ GdCUhd aj eYQaI CNHGQ GdQShds - (3eMeO Hf Ydj Hf GdMSf Hf HTQ, CHh YHO Gddg, GdMcje GdJQePj , J (B320 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe GdMGaX SQGL GdOjf s
(3BNQgG (B:s
(3hQLhY GdYHO Edi QHg ef aVdg ace ef ePfH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B315s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs